Changes in Glucose Metabolism and Atherogenic Risk Factors in Diabetic Patients’ First-degree Relatives - María Teresa González Pedroso; Elizabeth Remis Rodríguez; Marlene Ferrer Arrocha; Marisela Nuez Villar; Ingrid Rodríguez Crespo; Héctor Pérez Assef (Revista Finlay)
Foundation: diabetes mellitus is one of the diseases with the highest morbidity and mortality among non-communicable chronic conditions and its prevalence in individuals with a first-degree family history is high. Objective: to describe the alterations in glucose metabolism and the atherogenic risk factors present in diabetic patients’ first-degree relatives of a medical office. Method: a descriptive cross-sectional study was carried out between January 2020 and January 2022, which included first-degree relatives of type 2 diabetic patients, dispensed at medical office No. 10 belonging to the Héroes del Moncada University Policlinic from the Plaza de la Revolución municipality, 122 patients older than 19 years old were studied. The following variables were analyzed: age, sex, and skin color, atherogenic risk factors, and changes in carbohydrate metabolism. Results: female patients and the age group 19 and 39 years old predominated. The most frequent risk factor was dyslipidemia, present in 43,4 % followed by arterial hypertension and overweight/obesity. Alterations in glucose metabolism occurred in 74,6 % of the patients, with a predominance of altered fasting glycemia in 30,3 % and 11,5 % diagnosed with diabetes mellitus. Conclusions: the alterations in glucose metabolism and the atherogenic risk factors detected reveal the association between genetic and environmental factors in the development of the disease and the importance of developing prevention strategies from an early age of life.